2017
DOI: 10.15376/biores.12.3.5878-5895
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents and Toxicity Screening of Three Aromatic Plant Species from Peninsular Malaysia

Abstract: Medicinal and aromatic plants (MAPs) are widely valued for their aromas, tastes, and treatments for various human illnesses. The chemical constituents and toxicity content of three aromatic plant species, Syzygium polyanthum Wight (Walp.), Monocarpia marginalis (Scheff.) J. Sinclair, and Chromolaena odorata (L.) R.M. King & H. Rob, were determined, via gas chromatography (GC) with mass spectrometry (MS), and flame ionization detector (FID). Altogether, 116 compounds were identified in the essential oils and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
(49 reference statements)
1
6
1
1
Order By: Relevance
“…It was observed that methanol gave the highest yield among the four extracts while hexane gave the lowest yield. In agreement with this finding, Jumaat et al 28 reported that their extraction with n-hexane, a solvent with a polarity index (P') of 0.1 gave low extraction yield as compared to methanol. Extraction with n-hexane is crucial to break down the cell wall which is coated with the non-polar phospholipids.…”
Section: Yield Of Extractionmentioning
confidence: 54%
“…It was observed that methanol gave the highest yield among the four extracts while hexane gave the lowest yield. In agreement with this finding, Jumaat et al 28 reported that their extraction with n-hexane, a solvent with a polarity index (P') of 0.1 gave low extraction yield as compared to methanol. Extraction with n-hexane is crucial to break down the cell wall which is coated with the non-polar phospholipids.…”
Section: Yield Of Extractionmentioning
confidence: 54%
“…The results of in vivo research with a duration of administration of bay leaf extract for 14 days at a dose of 2.2 mg can increase Hb levels by 2.4 g%, an amount of 4.4 mg by 1.55 g%, and a dose of 6.6 mg with an increase in Hb levels of 2.65 g% in Wistar strain mice, comparable to the standard treatment of blood supplemented tablets [13]. Bay leaves are safe for consumption because they are proven not to show toxic, teratogenicity, and genotoxic effects in experimental animal [14]. However, the micronutrient content in bay leaves extract is still unknown.…”
Section: Introductionmentioning
confidence: 82%
“…Mutagenicity study of C. zeylanicum had also been done previously using the Ames and rec assay whereby the results showed no mutagenic effect either in the presence or absence of S9 in both assays 20 , 21 . As for S. polyanthum , the genotoxicity study of its extract was evaluated using a comet assay and the result showed no genotoxic effect that can cause DNA damage 22 . Meanwhile, an extract of C. xanthorrhiza was reported to show anti-mutagenic activity through the Ames assay 23 .…”
Section: Discussionmentioning
confidence: 99%